Peran Manajemen Kegiatan Ekstrakurikuler dalam Meningkatkan Prestasi Peserta Didik - Sitti Madinah; Lisa Nursita; Syamsuddin (Faculty of Tarbiyah and Teacher Training, 2023)
This study aims to find out how the role of extracurricular activity management can improve student achievement at MAN 1 Polewali Mandar. In this study using a qualitative research type. The data collection methods were conducted by interview and documentation. Data sources are primary data sources and secondary data sources. The role of management of extracurricular activities; (a) Management of extracurricular activities planning includes determining the types of extracurricular activities and determining the budget, (b) Management of organizing extracurricular activities, determining teachers as supervisors of extracurricular activities, and establishing institutional structures, (c) Management of the implementation of extracurricular activities where extracurricular activities are carried out in daily, weekly, and annual work programs and the activeness of students participating in competitions, as well as training students' skills and developing academic and non-academic learning achievement (d) Management of extracurricular activities supervision includes evaluating each implementation of extracurricular activities and after they are carried out, as well as LPJ (Accountability Report). There are obstacles in the management of extracurricular activities when the implementation of extracurricular activities is very short, the budget, facilities and infrastructure are inadequate. The implications of this research; (1) It is hoped that the madrasah will archive every documentation of the achievements of extracurricular activities in the competition, and identify every student who excels. (2) It is hoped that the coach will be able to maintain the process of mentoring students.